Elucidating the role of MaBAM9b in starch degradation. (December 2022) - Liu, Juhua; Miao, Hongxia; Wang, Yudi; Zhang, Jianbin; Zhang, Jing; Zhen, Yunke; Wang, Jingyi; Jia, Caihong; Xu, Biyu; Li, Xinguo; Xie, Jianghui; Jin, Zhiqiang
Abstract: Banana is a typical starch conversion fruit. The high content of starch at harvest is quickly digested and converted to soluble sugars during the postharvest ripening process, ultimately contributing to fruit flavor. This process is regulated in a complex manner by genes and environmental factors. MaBAM9b is one of the main enzyme genes previously found by transcriptomic analysis to be highly expressed in banana fruit. However, its exact role in starch degradation remains unclear. Here, full-length MaBAM9b was isolated from banana fruit, and its subcellular localization, protein expression, and transient expression in banana fruit slices were investigated. In addition, sense and anti-sense MaBAM9b were transformed into rice ( Oryza sativa L. japonica . cv. 'Nipponbare') to identify the function of MaBAM9b . MaBAM9b was 1599 bp and encoded 532 amino acids. It contained two conserved domains of PLN02803 and glycosyl hydrolase family 14 and was localized in the chloroplast. The protein expression pattern of MaBAM9b remained consistently high throughout banana fruit ripening and starch degradation. Transient overexpression or inhibition of MaBAM9b in banana fruit greatly improved or suppressed starch degradation. Genetic modification of rice indicated that overexpression of MaBAM9b greatly improved starch degradation and seed germination, while inhibition of its expression suppressed these biological processes. These results support the key role of MaBAM9b in starch degradation and provide a target gene for banana fruit quality improvement and biological breeding. Highlights: MaBAM9b targeted into the chloroplast with conserved domains necessary for catalysis in starch degradation. MaBAM9b expression was positively correlated with starch degradation and fruit ripening. Over-expression of MaBAM9b greatly improved starch degradation. Inhibition of its expression obviously suppressed starch degradation.